Protocol for the process evaluation of the Promoting Activity, Independence and Stability in Early Dementia (PrAISED), following changes required by the COVID-19 pandemic. Issue 8 (27th August 2020) - Di Lorito, Claudio; Bosco, Alessandro; Goldberg, Sarah E; Nair, Roshan; O'Brien, Rebecca; Howe, Louise; van der Wardt, Veronika; Pollock, Kristian; Booth, Vicky; Logan, Pip; Godfrey, Maureen; Dunlop, Marianne; et al.
Abstract : Introduction: The Promoting Activity, Independence and Stability in Early Dementia (PrAISED) randomised controlled trial (RCT) is evaluating a home-based, face-to-face, individually tailored, activity and exercise programme for people living with dementia. Social distancing requirements following the COVID-19 pandemic necessitated rapid changes to intervention delivery. Methods and analysis: A mixed-methods process evaluation will investigate how the changes were implemented and the impact that these have on participants' experience. An implementation study will investigate how the intervention was delivered during the pandemic. A study on the mechanisms of impact and context will investigate how these changes were experienced by the PrAISED participants, their carers and the therapists delivering the intervention. The study will commence in May 2020. Ethics and dissemination: The PrAISED RCT and process evaluation have received ethical approval number 18/YH/0059. The PrAISED process evaluation will enable us to understand how distancing and isolation affected participants, their activity and exercise routines and whether the therapy programme could be continued with remote support. This will be valuable both in explaining trial results and also contribute to understanding and designing new ways of delivering home-based services and rehabilitation interventions for people with dementia and their carers. Trial registration number: ISRCTN15320670; Pre-results .